Teaching Factors Related to Happy Learning of Nakhon Pathom Rajabhat University Students - Phutjun, Chatpramon; Wichayawong, Wanlapa; Panyindee, Janjiraporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The objectives of this research were 1) to study happy learning level of Nakhon Pathom Rajabhat University Students; and 2) teaching factors related to happy learning of Nakhon Pathom Rajabhat University Students. The sample were 383 students including freshmen, sophomores and juniors of Nakhon Pathom Rajabhat University in the second semester of the academic year 2011. The Questionnaire was used as the tool for data collection. The data was analyzed in term of frequency, percentage, means, standard deviation and correlation coefficient. The results from the study indicated that: 1. The happy learning of Nakhon Pathom Rajabhat University’s students was at the high level (M = 3.82, S.D = 0.51). 2. Teaching factors statistically related to happy learning of Nakhon Pathom Rajabhat University students at the moderate level (r=.411) with the statistical significance at .01 level. Teaching factors arranged from the highest to lowest levels were as follows: teaching process (r=.399), facilitation (r = .322) and characteristics of lecturers (r = .297). Article history : Accepted 2 May 2014 SIMILARITY INDEX = 0.00